Educação afetiva nos anos iniciais do ensino fundamental: mobilização de afetos dos professores de 1º e 2º ano - Sipp, Geiza Margarete Martins (My University, 2024)
This dissertation is linked to the Graduate Program in Education at the University of Caxias do Sul, within the research line Educational Processes, Language, Technology, and Inclusion. It is impossible to talk about education without addressing affection, as educational processes involve affective relationships, where we are constantly influenced by interactions with other individuals, objects, and environments. The objective of this research was to investigate how the meanings of 1st and 2nd-grade teachers in the Early Years of Elementary Education in the municipal network of Veranópolis (RS) are constituted regarding affective education and how these meanings are mobilized in the pedagogical practices of these teachers. This is a qualitative study. The theoretical framework is primarily composed of: Wallon (2007), Vigotsky (2000), Spinoza (2022), Juana Sancho Gil (2016), Fernando Hernández (2020), Celso Vasconcellos (2002), Bernard Charlot (2007), and Andy Hargreaves (2002). For the case study, we reference Yin (2005). The chosen investigation technique for data construction was the Focus Group, based on the work of Cruz Neto, Moreira, and Sucena (2002), from the narratives produced by five head teachers of 1st and 2nd-grade classes in the municipal network of Veranópolis (RS). For the analysis of the reports, content analysis by Bardin (2021) was used, which involves stages of pre-analysis, material exploration, results processing, inference, and interpretation. This research concludes that affective education is essential for the comprehensive development of students, highlighting the importance of forming affective bonds, respecting individuality, and valuing students' achievements. The need for continuous teacher training on the topic of affective education was recognized as fundamental, as well as overcoming challenges such as lack of time and bureaucratic overload, with the support of institutional backing. [resumo fornecido pelo autor]
Esta dissertação vincula-se ao Programa de Pós-Graduação em Educação da Universidade de Caxias do Sul, na linha de pesquisa Processos Educacionais, Linguagem, Tecnologia e Inclusão. Não se pode falar em educação sem falar em afeto, pois processos educativos envolvem relações afetivas, onde somos afetados o tempo todo nas interações com outros sujeitos, objetos e ambientes. Esta pesquisa teve como objetivo investigar como se constituem as significações de professores de 1º e 2º ano dos Anos Iniciais do Ensino Fundamental, na rede municipal de Veranópolis (RS), sobre educação afetiva e de que modo elas são mobilizadas nas práticas pedagógicas desses professores. Trata-se de uma pesquisa qualitativa. O aporte teórico é constituído, principalmente, por: Wallon (2007), Vigotsky (2000), Spinoza (2022), Juana Sancho Gil (2016), Fernando Hernández (2020), Celso Vasconcellos (2002), Bernard Charlot (2007) e Andy Hargreaves (2002). Para o estudo de caso, parte-se de Yin (2005). A técnica de investigação escolhida para a construção dos dados foi o Grupo Focal, fundamentada por Cruz Neto, Moreira e Sucena (2002), a partir das narrativas produzidas por cinco professoras titulares de turmas do 1º ano e 2º ano da rede municipal de Veranópolis (RS). Para a análise dos relatos, utilizou-se a análise de conteúdo, de Bardin (2021), que envolve etapas de pré-análise, exploração do material, tratamento dos resultados, inferência e interpretação. Com esta investigação, conclui-se que a educação afetiva é essencial para o desenvolvimento integral dos alunos, destacando a importância de formar vínculos afetivos, respeitar a singularidade e valorizar as conquistas dos alunos. A necessidade de formação continuada para os professores, na temática de educação afetiva foi reconhecida como fundamental, assim como a superação de desafios, como a falta de tempo e sobrecarga burocrática, a partir do apoio institucional. [resumo fornecido pelo autor]
Keywords: Educação afetiva; Ensino fundamental; Professores de ensino fundamental; Educação inclusiva; Affective education; Elementary school; Elementary school teachers; Inclusive education